Cross-Sectional Study on Self-Efficacy and Spirituality in Relation to Subjective Well-Being Within Youth Living in Urban Slums - Fitriyani; Adi, Isbandi Rukminto (International Journal of Social Science and Religion (IJSSR), 2025)
Subjective well-being offers a meaningful lens to understand how individuals perceive their lives, particularly among youth in urban slums who face multiple structural barriers. This study examines the the relationship of self-efficacy and spirituality with subjective well-being among 385 young people aged 23–30 in slum settlements in Cipayung District, Depok. The research employed a quantitative approach using descriptive statistics, Kendall’s tau-b correlation, and odds ratio analysis. Results show that 80.0 percent of respondents were classified as having low subjective well-being. Both self-efficacy (p = 0.000) and spirituality (p = 0.002) were significantly associated with higher subjective well-being. The odds ratio for high self-efficacy was 5.44 (95% CI: 3.00–9.88), and for high spirituality was 2.10 (95% CI: 1.26–3.50). These findings highlight the importance of strengthening internal psychological capacities, such as belief in one’s abilities and spiritual orientation, to improve youth well-being in marginalized urban communities.